Analisis Penerapan Sistem Manajemen Kinerja di PT AAA - Amrina Rasyada; Dwi Idawati (Research Center and Case Clearing House PPM School of Management, 2021)
PT AAA is a logistics company with a strategic goal to become 4th Party Logistics in Indonesia. It needs to improve its business and human resource performances. Thus performance measurement system becomes a must for aligning business strategy with the individual performance so the company will achieve a competitive advantage and excels in the logistics industry competition. This study was designed to identify the management practice in the company by using performance management theory according to Aguinis (2014). This research uses qualitative and descriptive quantitative approaches with data collection methods: interviews, focus group discussions, surveys (Weiss Hartle, 1997), and document studies. The results of this research are in the planning phase, performance objectives are not cascaded from business strategy as well there is no performance plan meeting either. In the execution phase, it was found that the company doesnt conduct a scheduled formal performance meeting. In the appraisal phase, the employees are not involved in the appraisal process, and in the review phase, the performance results have not utilized effectively